The complete mitochondrial genome of Tambocerus sp. (Hemiptera: Cicadellidae). (2nd January 2017) - Yu, Pengfei; Wang, Mengxin; Cui, Lin; Chen, Xuexin; Han, Baoyu
Abstract: The complete mitochondrial genome of Tambocerus sp. (Hemiptera: Cicadellidae) from Zhejiang and Anhui provinces of China was sequenced. The total length of the mitogenome is 15 955 bp (GenBank accession no. KT827824) and consists of 22 transfer RNAs, 13 protein-coding genes, 2 ribosomal RNAs and 1 control region. The base composition of the heavy strand for A, T, C, and G is 41.39, 35.02, 14.00, and 9.59%, respectively. All of the protein-coding genes (PCGs) start with ATN. Five protein-coding genes use TAA as stop codons, four use TAG as stop codons, and others use incomplete stop codons ''T––'' or ''TA–''. The control region has a length of 1581 bp which is between rrnS and trnI genes with the AT content high to 85.96%. Phylogenetic analysis indicated that Tambocerus sp. was clustered in a closely related subgroup with Homalodisca vitripennis and Empoasca vitis . This is consistent with the result of the traditional taxonomy.